Watch Your Step! - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet describes the opportunity for architectural beauty that a staircase in one's home provides. Discusses a brief history of staircase architecture, then provides instruction for finishing a staircase with paint or stain. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Staircases; Paint materials; Staircases--Maintenance and repair; Interior decoration; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint